Wide-band modeling for dual-band coil of wireless power transfer system - Ran Li; Lin Li (2016 IEEE Conference on Electromagnetic Field Computation (CEFC), 2016)
Dual-band wireless power transfer (WPT) system will be one of the noticeable researches about WPT because of communication between the transmitting and receiving resonators. To realize dual bands, an extra compensation circuit (CSC) is inserted into the original WPT coil. In this paper, we establish wide-band model for dual-band WPT coil on the basis of vector fitting (VF) and partial element equivalent circuit (PEEC) method. Prototypes of dual-band coils are manufactured, and impedance of the CSC is measured. Measured results are approximated by VF, which show good fitting results.